Clinical Impact of after-consult clinic blood pressure: comparison with automated office blood pressure - Cheol Ho Lee; Ji Hun Ahn; Joon Ha Ryu; Woong Gil Choi (BMC, 2021)
Abstract Background It is most important to measure blood pressure (BP) exactly in treating hypertension. Recent recommendations for diagnosing hypertension clearly acknowledge that an increase in BP attributable to the "whitecoat response" is frequently associated with manual BP recordings performed in community-based practice. However, there was no data about after-consult (AC) BP that could reduce whitecoat effect. So we evaluated before-consult (BC) and AC routine clinic BP and research based automated office blood pressure (AOBP) measured. Methods The study population consisted of 82 consecutive patients with hypertension between April 2019 and December 2019. We measured routine clinic BP and AOBP before and after see a doctor, respectively. Seated blood pressure and pulse are measured at each time after a rest period using an automated device as it offers reduced potential for observer biases. AOBP was measured and measuring BP 3 times un-observed. We compared each BP parameter for identifying exact resting BP state. Results There was significant difference between BC and AC systolic BP (135.37 ± 16.90 vs. 131.95 ± 16.40 mmHg, p = 0.015). However there was no difference in the BC and AC diastolic blood pressure (73.75 ± 11.85 vs. 74.42 ± 11.71 mmHg, p = 0.415). In the AOBP comparison, there was also significant difference (BC systolic AOBP vs. AC systolic AOBP, 125.17 ± 14.41 vs. 122.98 ± 14.09 mmHg, p = 0.006; BC diastolic ABOB vs. AC diastolic AOBP, 71.99 ± 10.49 vs. 70.99 ± 9.83, p = 0.038). Conclusions In our study, AC AOBP was most lowest representing resting state. Although AC BP was higher than BC AOBP, it might be used as alternative measurement for reducing whitecoat effect in the routine clinical practice.